MINIMALLY INVASIVE SINGLE FLAP APPROACH WITH CONNECTIVE TISSUE WALL FOR PERIODONTAL REGENERATION - Kamen Kotsilkov (Peytchinski Publishing, 2017)
INTRODUCTION: The destructive periodontal diseases are among the most prevalent in the human population. In some cases, bony defects are formed during the disease progression, thus sustaining deep periodontal pockets. The reconstruction of these defects is usually done with the classical techniques of bone substitutes placement and guided tissue regeneration. The clinical and histological data from the recent years, however, demonstrate the relatively low regenerative potential of these techniques. The contemporary approaches for periodontal regeneration rely on minimally invasive surgical protocols, aimed at complete tissue preservation in order to achieve and maintain primary closure and at stimulating the natural regenerative potential of the periodontal tissues. AIM: This presentation demonstrates the application of a new, minimally invasive, single flap surgical technique for periodontal regeneration in a clinical case with periodontitis and a residual deep intrabony defect. MATERIALS AND METHODS: A 37 years old patient presented with chronic generalised periodontitis. The initial therapy led to good control of the periodontal infection with a single residual deep periodontal pocket medially at 11 due to a deep intrabony defect. A single flap approach with an enamel matrix derivate application and a connective tissue wall technique were performed. The proper primary closure was obtained. RESULT: One month after surgery an initial mineralisation process in the defect was detected. At the third month, a complete clinical healing was observed. The radiographic control showed finished bone mineralisation and periodontal space recreation. CONCLUSION: In the limitation of the presented case, the minimally invasive surgical approach led to complete clinical healing and new bone formation, which could be proof for periodontal regeneration.